An examination of different perspectives on philanthropic corporate social responsibility: A Q methodology approach. Issue 4 (23rd October 2019) - Chung, Angie; Kinsey, Dennis F.
Abstract : Purpose: The purpose of this study is to identify different perspectives on philanthropic corporate social responsibility (CSR) activities by using the mixed-method approach and Q methodology. In addition, this study examines why people consider the revealed perspectives to be important factors. Design/methodology/approach: In this study, the authors used a structured sampling of 30 CSR-related statements (a Q sample) and had participants rank-order the statements from "most important" (+4) to "most unimportant" (−4). Findings: The results, from the factor analysis and correlation using the Q method software program PQMETHOD, revealed two distinctive perspectives. The first group emphasized the importance of supporting environmental-related activities. The second group ranked supporting arts-related activities as the most important factor of philanthropic CSR activities. Research limitations/implications: The goal of Q methodology is not the generalizability of the results but to identify the different views that exist regarding a topic, even minority ones. The findings are discussed in terms of practical implications for how this framework can be used to understand the subjective papers of different types of stakeholders. Originality/value: This study identifies the different perspectives that exist regarding philanthropic CSR activities by using Q methodology, which is a good alternative to other research methods that provides a unique way of uncovering subjectivity from the participants' point of view.